PURCHASE DECISION: E-PROMOTION AND SERVICE QUALITY - Rauf, Abdul (Univesitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of e-promotion and service quality on purchasing decisions. This type of research is quantitative research. The sample amounted to 60 respondents, with the data collection technique used was Nonprobability Sampling, the data analysis technique used SPSS version 21. The results showed that partially there was a positive and significant influence of the e-promotion variable on purchasing decisions with a tcount of 5.417> 2,000 t table, service quality had a positive and significant effect on purchasing decisions with a tcount of 5.207> 2,000 t table. Simultaneously the results of data processing show that e-promotion and service quality have a positive and significant effect on purchasing decisions, the Fcount value is 17.706> 3.16 Ftable. With the value of the multiple regression equation Y = 14.584 + 0.361 + 0.293. With a determination coefficient of 38.3%, the rest is influenced by other factors.